Nearly extremal apparent horizons in simulations of merging black holes. (26th February 2015) - Lovelace, Geoffrey; Scheel, Mark A; Owen, Robert; Giesler, Matthew; Katebi, Reza; Szilágyi, Béla; Chu, Tony; Demos, Nicholas; Hemberger, Daniel A; Kidder, Lawrence E; Pfeiffer, Harald P; Afshari, Nousha
Abstract: The spin angular momentum S of an isolated Kerr black hole is bounded by the surface area A of its apparent horizon:, with equality for extremal black holes. In this paper, we explore the extremality of individual and common apparent horizons for merging, rapidly spinning binary black holes. We consider simulations of merging black holes with equal masses M and initial spin angular momenta aligned with the orbital angular momentum, including new simulations with spin magnitudes up to . We measure the area and (using approximate Killing vectors) the spin on the individual and common apparent horizons, finding that the inequality is satisfied in all cases but is very close to equality on the common apparent horizon at the instant it first appears. We also evaluate the Booth–Fairhurst extremality, whose value for a given apparent horizon depends on the scaling of the horizon's null normal vectors. In particular, we introduce a gauge-invariant lower bound on the extremality by computing the smallest value that Booth and Fairhurst's extremality parameter can take for any scaling. Using this lower bound, we conclude that the common horizons are at least moderately close to extremal just after they appear. Finally, following Lovelace et al (2008 Phys. Rev. D 78 084017 ), we construct quasiequilibrium binary-black hole initial data with 'overspun' marginally trapped surfaces with . We show that the overspun surfaces are indeed superextremal: our lower bound on their Booth–Fairhurst extremality exceeds unity. However, we confirm that these superextremal surfaces are always surrounded by marginally outer trapped surfaces (i.e., by apparent horizons) with . The extremality lower bound on the enclosing apparent horizon is always less than unity but can exceed the value for an extremal Kerr black hole.